Precious Play in Morten Søndergaard’s Ordapotek - Steponavičiūtė, Ieva (Scandinavistica Vilnensis, 2014)
After touching upon some theoretical aspects of play/game – text analogy, the article focuses on the manifestations of play in the project Wordpharmacy by the Danish author Morten Søndergaard, including its not problem-free relation to the image of the curious child at play.
Keywords: literature and play; Morten Søndergaard; Ordapotek; Word pharmacy